Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1519/jsc.0b013e3181f00c7c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of High-Speed Power Training and Traditional Slow-Speed Resistance Training in Older Men and Women

Abstract: Muscle power, the product of force × velocity, is a critical determinant of function in older adults. Resistance training (RT) at high speed has been shown to improve peak muscle power in this population; however, different functional tasks may benefit from the improvement of power at values other than "peak" values, for example, tasks that require a greater velocity component or a greater force component. This study compared the effect of high-speed RT on muscle performance (peak power [PP] and its components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 30 publications
5
58
1
2
Order By: Relevance
“…Our findings indicate that older adults with knee OA improved muscle performance measures similarly to community-dwelling older adults without a diagnosis of knee OA (19). In the present study, improvements in muscle power were greater in HSPT compared with SSST.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings indicate that older adults with knee OA improved muscle performance measures similarly to community-dwelling older adults without a diagnosis of knee OA (19). In the present study, improvements in muscle power were greater in HSPT compared with SSST.…”
Section: Discussionsupporting
confidence: 60%
“…A critical component of muscle power development is the speed at which force is applied. Our laboratory has shown that high-speed power training (HSPT) at low external resistances (40% of the 1-repetition maximum [1RM]) significantly improved muscle performance (peak power [PP] and PP velocity) (19) and high-speed function (20) compared to traditional slow-speed RT at high external resistances (80% of the 1RM) in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Lower extremity muscle power has been recently posited as a more discriminating variable for understanding the relationships between impairments, functional limitations, and resultant disability with aging (Reid and Fielding 2012). Several recent studies also suggest that high-speed training is clinically relevant to maintain functional abilities in older women (Sayers and Gibson 2010;Pereira et al 2012;Reid and Fielding 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Some authors suggest that intervention strategies created to increase muscle power through fast movements should be implemented in exercise programs for PD 5 . Power training programs with low load improve strength, muscle power, balance, contraction speed, and time of movement in older adults [6][7][8] . In these subjects, loads equal to 40% of one maximal resistance (1MR) were able to increase muscle power because of the gains in movement speed 8,9 .…”
Section: Introductionmentioning
confidence: 99%